Characterization of zolbetuximab in pancreatic cancer models. (2nd January 2019) - Türeci, Ӧzlem; Mitnacht-Kraus, Rita; Wöll, Stefan; Yamada, Tomohiro; Sahin, Ugur
ABSTRACT: In healthy tissue, the tight junction protein Claudin 18.2 (CLDN18.2) is present only in the gastric mucosa. Upon malignant transformation of gastric epithelial tissue, perturbations in cell polarity lead to cell surface exposure of CLDN18.2 epitopes. Moreover, CLDN18.2 is aberrantly expressed in malignancies of several other organs, such as pancreatic cancer (PC). A monoclonal antibody, zolbetuximab (formerly known as IMAB362), has been generated against CLDN18.2. In a phase 2 clinical trial (FAST: NCT01630083), zolbetuximab in conjunction with chemotherapy prolonged overall and progression-free survival over chemotherapy alone and improved quality of life. In this study, the mechanism of action and antitumor activity of zolbetuximab were investigated using nonclinical PC models. Zolbetuximab bound specifically and with strong affinity to human PC cells that expressed CLDN18.2 on the cell surface. In ex vivo systems using immune effector cells and serum from healthy donors, zolbetuximab induced antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC), resulting in the lysis of cultured human PC cells. The amplitude of ADCC and CDC directly correlated with cell surface CLDN18.2 levels. The chemotherapeutic agent gemcitabine upregulated CLDN18.2 expression in cultured human PC cells and enhanced zolbetuximab-induced ADCC. In mouse xenograft tumors derived from human PC cell lines, including gemcitabine-refractory ones, zolbetuximab slowed tumor growth, benefited survival, and attenuated metastases development. The results presented here validate CLDN18.2 as a targetable biomarker in PC and support extension of the clinical development of zolbetuximab to patients with CLDN18.2-expressing PC.